Green synthesis and characterization of gold nanoparticles using pomegranate peel extract for inhibition of calcium oxalate crystals and uropathogenic bacteria - Mundhewadikar, Dhananjay M.; Bhalerao, Minal R.; Vairale, Shiva; Sabir, Safiya; Mote, Chandrashekhar; Chowdhury, Chiranjit; Agawane, Sachin B. (BioNanoScience, 2025)
This study explores the therapeutic potential of pomegranate peel extract (PPE) and its gold nanoparticle conjugate (PPE-AuNP) in the prevention and treatment of urolithiasis. Pomegranate peels collected from four agro-climatic zones of India exhibited consistent methanolic extract yields (10–17%) and total phenolic content, with the highest levels observed in the West zone. Green synthesis of PPE-AuNPs was confirmed through UV–Vis spectroscopy (λmax = 522 nm), DLS (38.2 ± 2.1 nm), zeta potential (-33.66 ± 2.97 mV), and TEM imaging, which showed uniform spherical nanoparticles. Characterization confirmed that PPE-AuNPs were crystalline and phytochemically capped. FTIR shifts in O–H, C = O, and C–O bands, along with a ~ 500 cm-1 Au–O/N vibration, confirmed phytochemical-mediated reduction and stabilization. XRD revealed an FCC structure with a dominant (111) plane, indicating high crystallinity. The synthesized nanoparticles demonstrated antioxidant activity with an IC50 of 21.53 µg/mL, superior to PPE and AuNP alone. In vitro calcium oxalate crystallization assays revealed significant crystal inhibition by PPE-AuNPs, confirmed via E-SEM, EDAX, and XRD analyses. Antibacterial studies against E. coli, K. pneumoniae, S. aureus, and uropathogenic E. coli showed MIC values of 31.25–62.5 µg/mL for PPE and PPE-AuNPs, with negligible activity from AuNP alone. In vivo studies in ethylene glycol-induced urolithiatic rats revealed significant improvement in urinary parameters, renal biochemistry (creatinine, urea, SGPT, SGOT), hematological markers, and histopathology, especially in the PPE-AuNP-treated group. PPE-AuNP treatment normalized urinary appearance, reduced serum creatinine and blood urea nitrogen (BUN), and restored renal architecture with minimal degeneration. The enhanced therapeutic effects of PPE-AuNPs are attributed to their bioactive phenolic surface ligands and colloidal stability. Overall, this study demonstrates the synergistic efficacy of PPE-AuNPs as a potent, green nanotherapeutic agent for urolithiasis, offering antioxidant, antibacterial, and nephroprotective effects with promising translational relevance.